한의학에서 신경정신과 질환의 증례논문 동향분석 - 허은정(Eun Jung Heo); 한창현(Chang Hyun Han); 김우영(Wu Young Kim); 박상영(Sang Young Park); 전원경(Won Kyung Jeon) (동의생리병리학회지, 2011)
This study was aimed to review the trend of case reports of neuropsychiatry disease. The case reports were collected by retrieving Journal of Oriental Neuropsychiatry and analyzing period were from 1990 to 2010. We analyzed them for publish year, research institution, patients, sorts of diseases, pattern identification diagnosis, instrument, treatment period, sorts of treatments, and treatment with western medicine. We analyzed 142 case reports and there were many kinds of neuropsychiatry diseases and instruments that were evaluated the process. The reserchers used various treatment with oriental medicine. However, the number of case reports have decreased since the year of 2008. Most of the research institutions were university and general oriental medical hospital and the portion of private hospitals was only 2.11%. For the development of practical clinical trial of oriental medicine, we needs more qualifying case report. We hope more reserchers for psychiatry disease of oriental medicine will be interested in the publication of case report and this will serve to produce advance of oriental medicine.